2021
DOI: 10.1136/bmjopen-2020-048462
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette advertising exposure among South African adults in 2017: findings from a nationally representative cross-sectional survey

Abstract: ObjectivesIn South Africa, the Control of Tobacco and Electronic Delivery Systems Bill seeks to regulate e-cigarettes as tobacco products, including their advertising, promotion and sponsorship. Population data on e-cigarette advertising in South Africa are needed to inform public health programs, practice and policy. We examined self-reported e-cigarette advertising exposure during 2017.DesignCross-sectional.SettingHousehold-based survey.Participants3063 individuals who participated in the 2017 South African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A key area of public health significance is e‐cigarette advertising, marketing, and sponsorship. Several studies outside Nigeria have reported the impact of e‐cigarette advertising and marketing on attempts to quit vaping 48–50 and the potential to encourage individuals who have quit smoking to start vaping 79,80 . Hence, more studies are needed to provide scientific evidence on e‐cigarette advertising, marketing, and sponsorship in Nigeria, as such evidence is pivotal for proper planning, implementation, and evaluation of policies on e‐cigarettes in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…A key area of public health significance is e‐cigarette advertising, marketing, and sponsorship. Several studies outside Nigeria have reported the impact of e‐cigarette advertising and marketing on attempts to quit vaping 48–50 and the potential to encourage individuals who have quit smoking to start vaping 79,80 . Hence, more studies are needed to provide scientific evidence on e‐cigarette advertising, marketing, and sponsorship in Nigeria, as such evidence is pivotal for proper planning, implementation, and evaluation of policies on e‐cigarettes in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarettes entered the South African market in 2009 and are marketed as healthier alternatives to tobacco cigarettes ( Agaku et al, 2021a ; Muposhi and Dhurup, 2018 ). The market entry of e-cigarettes generated much debate related to risk profile including whether they should be classified as tobacco products or not ( Caruana, 2016 ; Visagie, 2017 ).…”
Section: Research Contextmentioning
confidence: 99%
“…The market entry of e-cigarettes generated much debate related to risk profile including whether they should be classified as tobacco products or not ( Caruana, 2016 ; Visagie, 2017 ). As of 2021, e-cigarettes were not yet regulated with the proposed Control of Tobacco and Electronic Delivery Systems Bill still pending ( Agaku et al, 2021a ). The Bill aims to regulate the manufacturing, designing and marketing of e-cigarettes in South Africa ( Agaku et al, 2021a ).…”
Section: Research Contextmentioning
confidence: 99%
“…13 ENDS also have emerged in South African market. [14][15][16] ENDS use prevalence is even lower in some low and middle-income countries (LMICs) such as Bangladesh and Zambia. 17 WHO recommends that ENDS be regulated to bar unproven health claims, minimise health risks, protect non-users from secondhand exposure and prevent initiation among youth (eg, by limiting advertising/sponsorship, restricting flavours), though the legal and regulatory status of these products differs widely by country.…”
Section: Electronic Nicotine Delivery Systemsmentioning
confidence: 99%
“…ENDS use is less common in Asia than in these other regions, with current use around 1.8% in China 13. ENDS also have emerged in South African market 14–16. ENDS use prevalence is even lower in some low and middle-income countries (LMICs) such as Bangladesh and Zambia 17.…”
Section: Brief History Of Tobacco Product Innovationmentioning
confidence: 99%